2011
DOI: 10.1039/c0ib00089b
|View full text |Cite
|
Sign up to set email alerts
|

Topographic enhancement mapping of the cancer-associated breast stroma using breast MRI

Abstract: In animal and laboratory models, cancer-associated stroma, or elements of the supporting tissue surrounding a primary tumor, has been shown to be necessary for tumor evolution and progression. However, little is understood or studied regarding the properties of intact stroma in human cancer in vivo. In addition, for breast cancer patients, the optimal volume of local tissue to treat surrounding a primary tumor is not clear. Here, we performed an interdisciplinary study of normal-appearing breast tissue using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…The monoexponential ADC showed little variation with distance from the tumor, in agreement with [6]. The pseudodiffusion fraction, f p , decreased with distance from the tumor (Figure 3b), consistent with lower microvessel density [3] and previous DCE data [2]. These IVIM parameters suggest that the smaller contribution of vascular perfusion to the signal further from the tumor is compensated for by freer diffusion in the extravascular space, resulting in a similar calculated ADC value throughout the stroma when a two-point ADC method is used.…”
Section: Data Fittingsupporting
confidence: 64%
See 2 more Smart Citations
“…The monoexponential ADC showed little variation with distance from the tumor, in agreement with [6]. The pseudodiffusion fraction, f p , decreased with distance from the tumor (Figure 3b), consistent with lower microvessel density [3] and previous DCE data [2]. These IVIM parameters suggest that the smaller contribution of vascular perfusion to the signal further from the tumor is compensated for by freer diffusion in the extravascular space, resulting in a similar calculated ADC value throughout the stroma when a two-point ADC method is used.…”
Section: Data Fittingsupporting
confidence: 64%
“…Furthermore, there was no significant difference between ADC in stroma near (2-5 mm) and far (9-13 mm) from the tumor. This is somehwat puzzling since microvessel density decreases with distance from the tumor [3] and the protein content and density of the extracellular matrix also vary. This may be because ADC lacks specificity to microstructural changes: a decrease in vascular pseudodiffusion can be compensated for by faster diffusion in the extravascular space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively high signal enhancement ratio values around the tumor have been associated with more ipsilateral recurrence in patients with ductal carcinoma in situ (7). Increase in near-tumor signal enhancement ratio has also been associated with increased microvessel density (27). To our knowledge, association between BREAST IMAGING: Parenchymal Enhancement of Contralateral Breast in Invasive Breast Cancer van der Velden et al has not yet been reported.…”
Section: Discussionmentioning
confidence: 90%
“…There is growing evidence that peritumoral microenvironmental changes may represent underlying mechanisms that affect tumor cell initiation, progression, and disease prognosis (11) and may affect surgical margins and risk of recurrence. Dynamic contrast enhanced magnetic resonance imaging has been used to identify this tumor-associated stroma (12).…”
Section: Introductionmentioning
confidence: 99%